2016
DOI: 10.1007/s11356-016-6760-8
|View full text |Cite
|
Sign up to set email alerts
|

Multielemental analysis of 20 mushroom species growing near a heavily trafficked road in Poland

Abstract: The aim of this work was to compare 10 mostly edible aboveground and 10 wood-growing mushroom species collected near a heavily trafficked road (approximately 28,000 vehicles per 24 h) in Poland with regard to their capacity to accumulate 26 trace elements (Ag, Al, As, Au, B, Ba, Bi, Cd, Co, Cr, Cu, Fe, Ga, Ge, In, Li, Mn, Ni, Pb, Re, Sb, Se, Sr, Te, Tl, and Zn) in their fruit bodies in order to illustrate mushroom diversity in element accumulation. All analyses were performed using an inductively coupled plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 32 publications
2
46
1
3
Order By: Relevance
“…Compared to other species, the fruiting bodies G. frondosa were revealed to be the greater source of Ca, Cu, Fe, Mg, Mn, P or Zn [13,55,56] and lower in the case of, e.g., sum of REEs [22]. All of these elements play a pivotal role in various physiological processes while their deficiencies have been implicated in the etiology of number of disorders [57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other species, the fruiting bodies G. frondosa were revealed to be the greater source of Ca, Cu, Fe, Mg, Mn, P or Zn [13,55,56] and lower in the case of, e.g., sum of REEs [22]. All of these elements play a pivotal role in various physiological processes while their deficiencies have been implicated in the etiology of number of disorders [57].…”
Section: Discussionmentioning
confidence: 99%
“…Mushrooms are well known to accumulate different elements, including potentially toxic metals and metalloids, and have been proposed as potential bioindicators of environmental pollution [13]. Numerous studies have addressed the chemical composition of wild species, including recently reported values of PGEs and REEs [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…15 Due to their saprotrophic properties, mushrooms can also be used as natural pollution indicators through element levels accumulated in their bodies due to substrate content during organic matter catabolism. 16,17 Elements such as Fe, Co, Cu, Mn, Mo, Sr, V and Zn that are required for living organisms in trace amounts can accumulate in living organisms over time and lead to undesirable consequences. 18 Thus, to determine the element levels of mushrooms is important to avoid the health problems that may arise due to their consumption via the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different species of the Ganoderma genus may require different conditions for growth and cultivation [29]. The element content in overgrown substrate or soil has been directly shown to affect their bioaccumulation in fruiting bodies [30]. It should also be noted that mushroom processing after harvest, particularly the conditions under which they are dried, can influence element content [31].…”
Section: Discussionmentioning
confidence: 99%